Does Bacillus thuringiensis Affect the Stress and Immune Responses of Rhynchophorus ferrugineus Larvae, Females, and Males in the Same Way? - Monica Celi; Debora Russo; Mirella Vazzana; Vincenzo Arizza; Barbara Manachini (Insects, 2022)
Bacillus thuringiensis (Bt) is considered a potentially useful entomopathogen against red palm weevil (RPW) Rhynchophorus ferrugineus. We compared the effects of Bt on mature larvae, females, and males. The pathogenicity of Bt was evaluated, estimating: Median Lethal Dose (LD50), Median Lethal Time (LT50), Total Hemocyte Count (THC), and Differential Hemocyte Counts (DHC), and the expression of the stress protein Heat Shock Protein 70 (Hsp 70) in hemocytes and the brain. Mortality exhibited a positive trend with the dosage and duration of exposure to Bt. Larvae were more susceptible than adults, and the LD50 of females was almost double the value of that of the larvae. LT50 value was higher for females than for males and larvae. Treatment with sub-lethal doses of Bt induced a decrease in THC in larvae, females, and males. In treated larvae, plasmatocytes decreased, while oenocytes and spherulocytes increased. In treated females, all types of hemocytes decreased, while in males the number of plasmatocytes decreased and granulocytes increased. We also registered the stress response directly on hemocytes showing that, already at 3 h after eating Bt, the expression of the stress protein Hsp 70 was modulated. This effect was also observed in brain tissue at 6 h after treatment. The results confirm that Bt treatment induces a pathogenic state in larvae and adults of both sexes, with effects after only a few hours from ingestion; however, the effects are different in magnitude and in type of target.